2018
DOI: 10.1002/ecs2.2192
|View full text |Cite
|
Sign up to set email alerts
|

Regional variations in occupancy frequency distribution patterns between odonate assemblages in Fennoscandia

Abstract: Abstract. Odonate (damselfly and dragonfly) species richness and species occupancy frequency distributions (SOFDs) were analyzed in relation to geographical location in standing waters (lakes and ponds) in Fennoscandia, from southern Sweden to central Finland. In total, 46 dragonfly and damselfly species were recorded from 292 waterbodies. Species richness decreased to the north and increased with waterbody area in central Finland, but not in southern Finland or in Sweden. Species occupancy ranged from 1 up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 61 publications
(110 reference statements)
10
13
1
Order By: Relevance
“…During winter, the regional species pool is smaller and many species are concentrated in urban habitats, at least in northern latitudes like in Finland. Some earlier studies have found some variability in the SOFD pattern among regions (Heatherly et al, 2007;Jokimäki et al, 2016;Korkeamäki et al, 2018). Our results suggest that the SOFD pattern slightly changed with the latitude, southern towns having more satellite species than the northern towns, probably due to a higher number of migratory species in the south.…”
Section: Species Occupancy Frequency Distribution Patternsupporting
confidence: 44%
See 1 more Smart Citation
“…During winter, the regional species pool is smaller and many species are concentrated in urban habitats, at least in northern latitudes like in Finland. Some earlier studies have found some variability in the SOFD pattern among regions (Heatherly et al, 2007;Jokimäki et al, 2016;Korkeamäki et al, 2018). Our results suggest that the SOFD pattern slightly changed with the latitude, southern towns having more satellite species than the northern towns, probably due to a higher number of migratory species in the south.…”
Section: Species Occupancy Frequency Distribution Patternsupporting
confidence: 44%
“…First, we study whether wintering birds will show either a bimodal or a unimodal satellite SOFD pattern. Because the wintering bird species pool is richer in southern than in northern Finland (Jokimäki et al, 1996;Väisänen, 2003), we expected that the relative number of satellite species will be higher in the southern than in the northern regions (Gaston et al, 1998;McGeoch and Gaston, 2002;Korkeamäki et al, 2018, but see Jokimäki et al, 2016. Second, we predicted that the SOFD pattern will differ between large-and small-sized towns as indicated in a previous study of European breeding birds in urban core zone areas (Jokimäki et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…All voucher specimens are stored in the RLAS laboratory at Halmstad University, Halmstad, Sweden. In two previous publications, the senior author (GS) has used the records of species occurrences (presence/absence) at the sites in 1997 to analyse biodiversity indicators 61 , and the data from three sampling years has been used as part of the dataset for investigating occupancy frequency distribution patterns in odonate species assemblies 62 . Here we use the data in a different way.…”
Section: Methodsmentioning
confidence: 99%
“…Describing SOFD patterns in species assemblages yields valuable information for evaluating ecological processes across different spatial (Jenkins, 2011; Jokimäki et al., 2016; Korkeamäki et al., 2018; McGeoch & Gaston, 2002; van Rensburg et al., 2000; Suhonen & Jokimäki, 2019) and temporal scales (Heino, 2008; Jenkins, 2011; McGeoch & Gaston, 2002; Suhonen & Jokimäki, 2019; Tokeshi, 1992). Such patterns are known to be affected by both methodological and biological factors (Brown, 1984; Collins & Glenn, 1997; Hui, 2012; McGeoch & Gaston, 2002; Mehranvar & Jackson, 2001; van Rensburg et al., 2000; Tokeshi, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, spatial variations in SOFD patterns have been more thoroughly investigated than temporal variation (Collins & Glenn, 1997; Korkeamäki et al., 2018; McGeoch & Gaston, 2002; Mehranvar & Jackson, 2001; Suhonen & Jokimäki, 2019), which has been analyzed in only a few studies. Most previous work has suggested that SOFDs tend to be rather stable over time (Collins & Glenn, 1997; Heino, 2008; Suhonen & Jokimäki, 2019), although seasonal variation in SOFD patterns has been reported in insects (Gaston & Lawton, 1989; Tokeshi, 1992).…”
Section: Introductionmentioning
confidence: 99%